2010 Sixth International Conference on Intelligent Information Hiding and Multimedia Signal Processing 2010
DOI: 10.1109/iihmsp.2010.14
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Two-Factor User Authentication in Wireless Sensor Networks

Abstract: Wireless sensor networks are widely used for applications such as environmental monitoring, airport safety, health care, etc. For user authentication, in 2009, Das proposed a two-factor user authentication scheme in wireless sensor networks. They claimed that this scheme provided efficiency, strong security, and user anonymity property. However, we find that Das's scheme is still vulnerable to masquerade attack and cannot achieve user anonymity. This paper will propose an improvement to remedy the weakness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 10 publications
0
77
0
Order By: Relevance
“…Huang, Chang [14] proposed an ''Enhancement Of Two Factor User Authentication In Wireless Sensor Network''. Das's [13] proposed a two-factor user authentication scheme in wireless sensor networks.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang, Chang [14] proposed an ''Enhancement Of Two Factor User Authentication In Wireless Sensor Network''. Das's [13] proposed a two-factor user authentication scheme in wireless sensor networks.…”
Section: Related Workmentioning
confidence: 99%
“…al. [3] Das [13] H e [ 16] Algahathour [17] Huang [14] Vaidya [15] Arikuma [12] Yeh [18] Sun et al [5] Our security framework can effectively defend against the Sybil attack, the node replication attack, and the wormhole attack by including the security time stamp in our protocol, a new node is only allowed to join the sensor network during its time stamp length. After that it becomes an old node.…”
Section: Communication Costmentioning
confidence: 99%
“…We also illustrate how [8] is vulnerable to parallel session and privileged-insider attacks and how it does not provide mutual authentication and password change features. Additionally, we explain how [9] is defenseless against parallel session, privileged-insider, and gateway-node bypassing attacks, does not offer a password change mechanism, and has a serious vulnerability in its mutual authentication mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Nyang and Lee [7] identified that Das' protocol was vulnerable to offline password guessing and sensor node compromising attacks. Huang et al [8] also identified some limitations of Das' scheme, such as vulnerability from an impersonation attack. Additionally, [9] pointed out the absence of a mutual authentication feature in Das' protocol, while Khan and Alghathbar [10] pointed out more security flaws of Das' proposal, noting that it was vulnerable to privileged-insider and gateway-node bypassing attacks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation